Saponins of ginseng products: a review of their transformation in processing - Ye, Xian-Wen; Li, Chun-Shuai; Zhang, Hai-Xia; Li, Qian; Cheng, Shui-Qing; Wen, Jia; Wang, Xuan; Ren, Hong-Min; Xia, Liang-Jing; Wang, Xu-Xing; Xu, Xin-Fang; Li, Xiang-Ri (Frontiers in Pharmacology, 2023)
The primary processed product of ginseng is red ginseng. As technology advances, new varieties of red ginseng have arisen. Ginseng products, e.g., traditional red ginseng, sun ginseng, black ginseng, fermented red ginseng, and puffed red ginseng, are commonly used in herbal medicine. Ginsenosides are the major secondary metabolites of ginseng. The constituent of red ginseng products significantly changes in processed ginsengs, and several pharmacological activities increase dramatically compared to white ginseng. In this paper, we aimed to discuss ginsenoside research advancements, the pharmacological activity of various red ginseng products, and the ginsenoside transformation rule in red ginseng products. This article will help to highlight the diverse pharmacological properties of red ginseng products and aid in the future development of red ginseng industrialization.